Evaluating the variability of glacial lakes in the Kyrgyz and Teskey ranges, Tien Shan - Daiyrov, Mirlan; Kattel, Dambaru Ballab; Narama, Chiyuki; Wang, Weicai (Frontiers in Earth Science, 2022)
The northern Tien Shan Mountains are one of the most hazardous areas in Kyrgyzstan due to frequent glacial lake outburst floods (GLOFs). The current status of glacial lakes in this region has not been reported in recent years. Therefore, this study investigates the variations of glacial lakes in the Kyrgyz and Teskey ranges using Sentinel-2 and PlanetScope optical satellite images from 2017 to 2019. Results confirm that there are 800 glacial lakes, of which 351 were in the Kyrgyz and 449 were in the Teskey Range. We found seasonality in the character of glacial lakes, most of which have been found to be unstable during our observation period. 242 glacial lakes showed significant variations in area. We found 46 newly emerging glacial lakes, five of which have rapidly expanded in the year since they formed, while 18 were found to have vanished. Thirteen lakes were found to be short-lived or unstable. In this study, 14 lakes showed a significant expansion of area. Such large variations in the glacial lakes are closely linked to local geomorphological conditions, local climate and glacier melt. We also identified a significant shift in the number of glacial lakes at altitudes over 3500 m asl. It is associated with the mountain permafrost zone and variations of the glacier terminus. The current study recommends detailed investigation of glacial lakes in each season with the use of remote sensing and field surveys.